Research on the Preparation of Microbial Capsules by Epoxy Resin-Coated Bacillus pasteurii - Yingying Hu; Weitao Liu; Xinlei Jia; Lanjuan Xu; Jianjun Shen; Xiangming Hu (Shock and Vibration)
With the increasing number of underground engineering construction projects such as coal mining, tunnel, and subway, water inrush disasters occur more and more frequently. Inspired by the phenomenon of microbial mineralization and diagenesis, microbial-induced calcium carbonate precipitation (MICP) is used to repair cracks in cement-based materials, which provides a new idea to solve the problem of water inrush. To investigate the self-healing properties of microbial capsules, this paper selected epoxy resin E-51 cured by DMP-30 as the wall material and Bacillus pasteurii as the core materials for experiments. In this paper, a single-factor method was adopted to determine the optimal preparation process of microbial capsules and the oil-phase separation method to prepare the microbial capsules. The effects of various factors on the experimental results under different core-wall ratios, reaction time, reaction temperatures, and agitation rates were analyzed. Microbial capsules were analyzed by Fourier transform infrared spectroscopy and optical microscopy to explore the functional groups and features of microbial capsules. The experimental results showed that the microbial capsules achieved the best performance with a core-to-wall ratio of 1 : 3, a reaction temperature of 50°C, a reaction time of 40 min, and a stirring rate of 300 rpm. Meanwhile, we determined the spore survival rate of microbial capsules and finally studied the waterproofness, storage stability, and rupture under the pressure of microbial capsules. We concluded that microbial capsules have high-efficiency and self-healing properties.